Case review post partum vulvo-vaginal haematomas, options of management - Lim PS,; Nirmala CK,; Shafiee MN,; Lim YH,; Rozman Z,; Mohd Hashim O,; Zainul RAZ,; Muhammad Abdul Jamil MY, (Department of Surgery, UKM Medical Centre, 2011)
Vulvo-vaginal haematomas are not an uncommon obstetric complication. Despite advances in obstetric care, practice and technique, vulvo-vaginal haematomas do occur especially in complicated vaginal deliveries. Various management options are available for vulvo-vaginal haematomas. We describe three cases of vulvo-vaginal haematomas with different severity and presentations which were managed in different manners i.e. local haemostasis control, laparotomy with hysterectomy, and transarterial embolisation. The choice of treatment options would mainly depend on the clinical presentations, availability of expertise as well as facilities. Early identification is crucial